The Number of Traditional Cardiovascular Risk Factors Is Independently Correlated with Disease Activity in Patients with Psoriatic Arthritis - Iván Ferraz-Amaro; Diana Prieto-Peña; Natalia Palmou-Fontana; David Martínez-López; Laura de Armas-Rillo; Alicia García-Dorta; Belén Atienza-Mateo; Ricardo Blanco; Susana Armesto; Miguel Á. González-Gay (Medicina, 2020)
Background and objectives: Psoriatic arthritis (PsA) is associated with several comorbidities, including among others an increased risk of cardiovascular (CV) disease, atherosclerosis, metabolic syndrome, hypertension dyslipidemia, and diabetes. The purpose of the present study was to determine how the number of CV risk factors correlates with disease related data such as disease activity. Materials and Methods: Cross-sectional study that encompassed 305 patients who fulfilled the CASPAR criteria for PsA were assessed for lipid profile, disease activity measurements, and the presence of six traditional CV risk factors (diabetes mellitus, dyslipidemia, hypertension, obesity, chronic kidney disease, and smoking status). A multivariable regression analysis, adjusted for age, sex, and disease duration, was performed to evaluate if the number of classic CV risk factors was independently related with specific features of the disease, including disease activity. Results: Disease duration was found to be higher, after adjustment for age and sex, in patients with 1 or 2, and 3 or higher CV factors, compared to those patients without CV risk factors. Similarly, DAPSA (Disease Activity in PSoriatic Arthritis score) was found to be independently upregulated in patients with a higher number of CV risk factors. In this sense, as DAPSA score increases the odds ratio (OR) of having 1 or 2 (OR 1.12 (95% confidence interval (CI) 1.03–1.21), p = 0.010), and 3 or higher (OR 1.15 (95% CI 1.04–1.26), p = 0.004) CV factors was significantly higher compared to no CV risk factors category. This was independently found after adjustment for age, sex, and disease duration. Conclusions: PsA patients with a higher number of CV risk factors exhibit an upregulated disease activity compared to those without them. This is independent of disease duration and other demographics factors.